Powtoon - Power point as a reading tool for infants and population with different illustred capacties - Muñoz Tibocha, Andrea Ximena (2021)
The research carried out on the utility of the tool POWTOON: Power point as a reading tool for infants and population with different capabilities, as Digital Educational Resource, comes from the concern that arises when detecting the difficulty during this process within the regular classrooms; where students who do not get to learn by the using of traditional methods are called as students with learning problems, and those with different characteristics are called as problematic students. This is why having knowledge of the methodology used by Dr. Glenn Doman, who affirms in his book: “How to teach your baby to read”.